Development Of Learning Videos With Video Cribe Software On Digital Simulation Lessons Class X Tktl 1 : Pengembangan Video Pembelajaran Dengan Software Videoscribe Pada Mata Pelajaran Simulasi Digital Kelas X Tktl 1 - Sabudin; Cindy Cahyaning Astuti (Academia Open, 2021)
In accordance to its essence, the creator of technology is done to facilitate and assist human life activities, such as in the learning process. The purpose of this study was to determine the feasibility of video learning media in digital simulation subjects. This research resulted in a learning video produk developed with videoscribe software that features hand animation writing or drawing something on the screen, such as the hand of the maker doing it himself, and can help students focus more and not get bored during the teaching and learning process so that the presentation of material can be conveyed to students. The research method applied uses R&D using a 4-D or four D model. The development of this learning video has been validated by media experts with a validity percentage of 80% in the “Eligible” category and from material experts with a 90% validity percentage with the “Very Appropriate” category. “,it is known that the product is in the category of” Appropriate “and can be used by students for learning as well as teachers in the learning process in class.”